2018
DOI: 10.1128/iai.00872-17
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Raft Partitioning of the Helicobacter pylori Pore-Forming Toxin VacA

Abstract: , a Gram-negative bacterium, is a well-known risk factor for gastric cancer. vacuolating cytotoxin A (VacA) is a secreted pore-forming toxin that induces a wide range of cellular responses. Like many other bacterial toxins, VacA has been hypothesized to utilize lipid rafts to gain entry into host cells. Here, we used giant plasma membrane vesicles (GPMVs) as a model system to understand the preferential partitioning of VacA into lipid rafts. We show that a wild-type (WT) toxin predominantly associates with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 91 publications
(155 reference statements)
0
25
0
Order By: Relevance
“…One model for VacA membrane assembly at low pH suggests the temporal order of membrane insertion, oligomerization, and pore formation (33). Besides, other experimental data demonstrated that VacA at neutral pH can also exhibit some weak binding to the cell membrane, suggesting an alternative pore-formation pathway at neutral pH with the oligomerization occurring before insertion and pore formation (14, 15). We also observed lower vacuolation activity (fewer vacuolated cells) of our purified VacA without acid treatment relative to that with acid treatment in HeLa cells ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One model for VacA membrane assembly at low pH suggests the temporal order of membrane insertion, oligomerization, and pore formation (33). Besides, other experimental data demonstrated that VacA at neutral pH can also exhibit some weak binding to the cell membrane, suggesting an alternative pore-formation pathway at neutral pH with the oligomerization occurring before insertion and pore formation (14, 15). We also observed lower vacuolation activity (fewer vacuolated cells) of our purified VacA without acid treatment relative to that with acid treatment in HeLa cells ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The current model of VacA-induced vacuolation proposes that VacA oligomers are first dissociated into monomers at low pH. This is then followed by the binding of VacA monomers to the host cell membrane, insertion into the lipid bilayer, oligomerization, and membrane channel formation (14). However, purified VacA without acid treatment also displays some degree of membrane binding (14, 15), suggesting that some VacA oligomers may exist as a “prepore” state for membrane binding before insertion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A hydrophobic region within the p33 domain is required for formation of membrane channels, and regions within both the p33 and the p55 domains mediate VacA oligomerization and binding to host cells (10)(11)(12)(13)(14)(15). VacA can bind the surface of epithelial cells via lipid rafts and is internalized into glycosylphosphatidylinositol-anchored protein (GPI-AP)-enriched early endosomal compartments (GEECs) before being trafficked to early and late endosomes (16)(17)(18)(19)(20)(21). VacA is reported to cause a wide range of cellular responses, including cell vacuolation, plasma membrane permeabilization, alteration of endosomal and lysosomal function, disruption of mitochondrial function, modulation of autophagy, apoptosis, necrosis, and inhibition of T-cell activation (reviewed in reference 4).…”
mentioning
confidence: 99%
“…For example, the raft domain is suggested to be a site for HIV budding, binding [32] and stabilization of rafts by cholera toxin (Ctx) and Shiga toxin (Stx) [33,34]. Also VacA, a vacuolating toxin of H. pylori, predominantly associates with the raft phase; however, this binding was found to be independent of oligomerization and pore-forming activity [10,35]. For example, an interesting observation was published recently indicating that H. pylori expression of the cgt gene encoding cholesterol-a-glucosyltransferase reduces cholesterol levels in infected gastric epithelial cells, which disrupts membrane rafts, blocking in turn IFNg signaling, allowing bacteria to escape the host inflammatory response [36].…”
Section: Membrane Raft Conceptmentioning
confidence: 99%